The use of English in Indonesia: Status and Influence - Gali Alrajafi (SIGEH ELT : Journal of Literature and Linguistics, 2021)
This research is a qualitative research which aims to describe the state of the use of English in Indonesia, in terms of language status and its influence on Indonesian society. To realize the purpose of this paper, the authors collected several news stories from national websites (such as Republika, Tribun News, detikNews, ANTARA, and Tempo) regarding the use of English in Indonesia as data that is explained and interpreted by descriptive qualitative analysis. The results of the study show that English is common and has massive use, even though it is still a foreign language. In fact, English has moved to improve its linguistic status, namely starting to act as a second language and the language of instruction.